Sediment-associated organic carbon and nitrogen inputs from erosion and irrigation to rice fields in a mountainous watershed in Northwest Vietnam - Slaets, J.I.F.; Schmitter, Petra S.; Hilger, T.; Hue, D.T.T.; Piepho, Hans-Peter; Vien, T.D.; Cadisch, Georg (Springer, 2016)
Maintaining indigenous nutrient supply and positive nutrient balances are key factors in sustaining rice yields. Irrigation systems act as conveyers for water, sediments and nutrients throughout landscapes, especially in mountainous, cultivated tropical areas where erosivity is usually high. Contributions of erosion and irrigation to the nutrient balance of paddy fields, however, are rarely assessed. In this study, a turbidity-based method was used to quantify sediment-associated organic carbon and nitrogen as well as dissolved nitrogen inputs from erosion and irrigation to a 13 ha rice area in Northwest Vietnam. The irrigation source is a surface reservoir, and both reservoir and irrigation channel are surrounded by permanent upland maize cultivation on the steep slopes. Additionally, organic carbon and nitrogen loads in paddy outflow were determined to obtain nutrient budgets. Irrigation contributed 90 % of sediment-associated organic carbon inputs and virtually all nitrogen inputs. Analysis of ammonium and nitrate in total nitrogen loads showed that 24 % of the total N inputs from irrigation to the rice area, or 0.28 Mg ha-1 a-1, were plant-available. Loads measured at the outlet of rice fields showed that paddies were a trap for sediment-associated nutrients: balancing inputs and outflow, a net load of 1.09 Mg ha-1 a-1 of sediment-associated organic carbon and 0.68 Mg ha-1 a-1 of sediment-associated nitrogen remained in the rice fields. Sediment-associated organic carbon and nitrogen inputs thus form an important contribution to the indigenous nutrient supply of rice in these maize-paddy systems, while the rice fields simultaneously capture nutrients, protecting downstream areas from the effects of land use intensification on surrounding slopes. These results underscore the importance of upland-lowland linkages in tropical, mountainous, erosion-prone areas.